Pengaruh Pemberian Air Perasan Jeruk Nipis (Citrus aurantifolia) Dalam Mengurangi Emesis Gravidarum pada Ibu Hamil Trimester I - Sari Lubis, Astri Yulia; Damayanti, Melly; Abilowo, Ashar (Citra Delima Scientific journal of Citra Internasional Institute, 2024)
Nausea and vomiting (emesis gravidarum) is a common disorder experienced by 50% of pregnancy, and is usually most severe in the first trimester of pregnancy. Nausea and vomiting occur 60-80% primigravida and 40-60% multigravida. One of the herbal plants that can reduce nausea vomiting is lime juice. Lime contains flavonoids contained in lime can also trigger peristaltic movements in the stomach so that the stomach can easily digest. The purpose of this study was to determine the effect of giving lime juice (Citrus aurantifolia) on emesis gravidarum in pregnant women in the first trimester of pregnancy. The research design used Quasi Experiment with a Non-Randomized Control Group Pretest-Posttest Design. Respondents were given of lime juice for 3 days then measured the frequency of nausea vomiting on day 1 and day 4. Samples are taken by consecutive sampling. Data collection by observation method using PUQE-24 hour scoring system. Data analysis using the Mann-Whitney test and obtained p-value = 0.000. The conclusion of a statistically significant influence is used the level of meaning ? = 0.05 or p<0.05. It is expected that midwives in the practice area will provide nonpharmacological therapy for lime juice as an effort as to treat emesis gravidarum.